Emission behaviour of modern heavy duty vehicles in real world driving. (28th October 2004) - Hausberger, Stefan; Rexeis, Martin
Within a national and two international research projects, a vehicle emission model was developed, which calculates emissions in real world driving from the engine emission maps by simulating engine power and engine speed. Influences of transient load changes on the emission level are taken into consideration by special functions. Model parameters are gained from a common measurement protocol on 72 engines. A main conclusion of the work was that EURO 2 and, to a smaller extend, EURO 3 HDV show significant higher NOx emission in real world driving than in the type approval tests.